Applying the Capability Approach to Improve the Quality of Medical Laboratory Test Results - Khanal, Kishor (Journal of Karnali Academy of Health Sciences, 2022)
Good medical laboratory test result relies on the appropriate quality assurance techniques, quality control mechanism, and quality management practices used in the laboratory. To ensure good quality results, a wide range of quality control tools and methods are applied. Along with them, equally important are the capabilities of humans, machines, and the chemicals used. Given the collective significance of these mechanisms, the joint promotion of those capabilities is the necessary condition for producing quality medical laboratory test results.